Preferential production of interferon-γ by CD4(+) T cells expressing the homing receptor integrin α(4)/β(7) - Abramson, Oren (Blackwell Science Inc, 2001)
Recent studies indicate that T helper type 1 (Th1) and 2 (Th2) lymphocytes differ in their expression of molecules that control T-cell migration, including adhesion molecules and chemokine receptors. We investigated the relationship between cytokine production and expression of the homing receptor integrin α(4)/β(7) on T cells. We began by analysing cytokine production by human CD4(+) CD45RA(–) memory/effector T cells following brief (4 hr) stimulation with phorbol 12-myristate 13-acetate (PMA) and ionomycin. α(4)/ [Image: see text] CD4(+) T cells were more likely to produce the Th1 cytokine interferon-γ (IFN-γ) than were α(4)/β(7)(−) CD4(+) T cells in all six subjects studied. In contrast, production of the Th2 cytokine interleukin-4 (IL-4) was similar on α(4)/ [Image: see text] and α(4)/β(7)(−) CD4(+) T cells. In addition, we found that human CD4(+) CD45RA(–) T cells that adhered to the α(4)/β(7) ligand mucosal addressin cell adhesion molecule-1 (MAdCAM-1) had a greater capacity to produce IFN-γ than did non-adherent cells, suggesting that the association between α(4)/β(7) expression and IFN-γ production has functional significance. These results suggested that primary activation under Th1-promoting conditions might favour expression of α(4)/β(7). We directly examined this possibility, and found that naïve murine CD4(+) T cells activated under Th1-promoting conditions expressed higher levels of α(4)/β(7) compared to cells activated under Th2-promoting conditions. The association between α(4)/β(7) expression and IFN-γ production by CD4(+) T cells may help to determine the cytokine balance when MAdCAM-1 is expressed at sites of inflammation in the intestine or elsewhere.